Protein-directed ribosomal frameshifting temporally regulates gene expression - Sawsan Napthine (Nature Portfolio, 2017)
Programmed −1 ribosomal frameshifting (−1 PRF) is a mechanism whereby specific signals within mRNAs direct ribosomes to shift into an alternative reading frame. Here the authors describe a mechanism of −1 PRF that is temporally regulated by a viral protein over the course of the virus replicative cycle.